СИНКРЕТИЗМ ВОПРОСИТЕЛЬНЫХ ПРЕДЛОЖЕНИЙ (НА МАТЕРИАЛЕ РУССКОГО И ЧЕШСКОГО ЯЗЫКОВ) - Flídrová, Helena (Przegląd Rusycystyczny, 2017)
In linguistics, syncretism is understood as asymmetry of language sign, i.e. discrepancy between the content and form of language phenomena, which implies their ambiguousness. This point of view is applied in the article in order to scrutinize and classify Russian and Czech syncretic interrogative sentences which are characterised by means of interrogative form and the meaning of request or challenge (e.g. Ты мне поможешь/не поможешь?, Чего ты не работаешь?!) or the meaning of declarative statement (e.g. Можно ли мириться с этими недостатками?). Ambiguousness of syncretic interrogative sentences is resolved in the context of communitation. Implementation of theory of grammatical syncretism in Russian and Czech comparative point of view seems to be promising in future